IOC consensus statement: The female athlete triad (Medicine and Science in Tennis, 2006)
Protecting the health of the athlete is the primary goal of the International Olympic Committee's Medical Commission (IOC MC). While athletes should be encouraged to strive for excellence, there is an obligation on the part of coaches, team physicians, other health care providers, International Federations, and sport governing bodies to recognise pressures, actions, and situations that may be detrimental to the athlete's health. One area of concern for many female athletes is the pressure to meet unrealistic weight or body fat levels. Some may respond to this pressure with excessive dieting and slip into disordered eating, which in turn can lead to a serious eating disorder such as anorexia nervosa or bulimia nervosa. Disordered eating can lead to low energy availability (an energy intake inadequate to meet energy expenditure), which can disrupt the reproductive cycle and result in amenorrhea. The combination of disordered eating and irregular menstrual cycles eventually lead to a decrease in endogenous oestrogen and other hormones, resulting in low bone mineral density hence the term "Female Athlete Triad" which is dealt with in this article.